Social Support and the Rehabilitation of Convicts in Calabar Correctional Service Centre, Cross River State, Nigeria - Akwaji, Fidelis Ngaji; Owan, Emeka Josephat; Idiege, Ahakiri Francis; Hassan, Ibrahim Muhammad; Jonathan, Opara Ikechukwu; Bassey, Abonor, Lazarus; Eno, Abang Paul; Williams, William Okon; Etta, Etta Oyen; Okorie, Chimaobi; Felix. O, Eteng,; Denwigwe, Chiaka Patience (Journal of Ecohumanism, 2024)
This study examined the nexus between social support and rehabilitation of convicts. Social support for convicts has not received adequate research interest in Nigeria within the field of corrections. This is because correctional administrators have not acknowledged the importance of social support to the adjustment pattern and rehabilitation of convicts. Literature on social support is western based. This study will contribute in narrowing the methodological gap created by dearth of literature on social support. Survey design was used for the study. The study used 318 respondents as its sample. Data collection was carried out using structured questionnaire. Statistical analysis involved the use of the Pearson Product Moment Correlation Coefficient (PPMCC) and simple percentage. The study’s results indicated a significant relationship between family, administrative and convicts supports and rehabilitation. Thus, it was recommended amongst others that; the family which is the basic unit of the society should always support one another.